Making Bioethanol From Cocoa Fruit Skin Waste By Hydrolysis Process Using Trichoderma Viride Mold - Tiska Oktavianis; Sofiyanita Sofiyanita (Indonesian Journal of Chemical Science and Technology (IJCST), 2019)
Cocoa fruit skin is one of the agricultural wastes can be used as raw material for bioethanol production. Because the cocoa fruit waste containing 39.45% crude fiber and 3.92% glucose. The purpose of this study was to determine the level of optimization of yeast and fermentation time to produce maximum ethanol content. In this study the hydrolysis process cocoa leather is done using fungi Trichoderma viride and fermentation process using yeast Saccharomyses cerevisiae. While for bioethanol concentration measurements performed using vinometer. The results showed that bioethanol fermentation time for 1, 3, 5 and 7 days using yeast levels 2, 4, 6 and 8 grams produce maximum ethanol fermentation at 3 days and 6 grams yeast levels. Produced a maximum ethanol content of 12%.